Solidaritas Sosial Masyarakat Petani Di Desa Wanareja Kabupaten Buru - M. Rusdi; Abdul Latif Wabula; Ivana Goa; Ismail Ismail (Jurnal Ilmiah Mandala Education (JIME), 2020)
This study aimed to describe the farmers' community's solidarity and both inhibiting and it's supporting factors. The next goal is to reveal the positive values contained in solidarity that is carried out by the farmers' community in the Village of Wanareja. This research uses a descriptive qualitative approach, and the data analysis was carried out by conducting a reduction, presentation, and verification of the data. The conclusion is drawn after the data presentation. Solidarity among farmers is based on humanity and a sense of responsibility for the interests of living together, mutual cooperation, and helping each other as an implementation of solidarity. The solidarity becomes a social unit to form of unity because of the social bond among peasants. The gotong royong and help each other is becoming a tool to measure the success of farming, it means that the more mutual cooperation and help each other run optimally among farmers, the more yields of the farmer will get. The kinship, culture, and religion are the supporting factors of the peasant solidarity, on the other side, the modernization and economic conditions are the inhibiting factors for the development of the solidarity attitude among the farmers' community.